In silico screening of compounds from the Bahia semiarid region for identification of potential inhibitors of the p38 MAPK protein (Research, Society and Development, 2020)
The P38 MAPK protein is mainly involved in the synthesis of the proinflammatory cytokines IL1 and TNF-alpha and is important in the maintenance and amplification of the inflammatory process. Therefore, this protein presents high potential as a pharmacological target in the search for new treatments for inflammatory diseases. In silico approach has been of great importance to develop quick and inexpensive target identification and way to discover new bioactive molecules. This study used a computer ligand-docking method to screen the compounds from the Bahia semiarid region in silico for their ability to inhibit p38 MAPK activity. The protein crystallographic structure of the p38 MAPK was obtained from the Macromolecular Protein Data Bank. Northeast semiarid molecules were obtained from the ZINC database. The database was screened and a set of 233 molecules were selected as candidates using filtering based on parameters of the rule of Lipinski and Verber. The docking was carried out using the program Autodock Vina in its default configuration. The compound with ZINC databank code: 91596862 was found the most promising compound acoording to their binding free energy value obtained in the docking experiments (11,1 Kcal.mol-1) Intermolecular interactions analysis suggested that Van der Waals interactions are crucial to the ZINC molecule 69481892 in the active site of the p38 MAPK protein. Data resulting from all dockings are significant, although it has low accuracy. Thus, the hypothetical results of these in silico studies should be confirmed by in vitro and/or in vivo tests.